2016
DOI: 10.3904/kjim.2015.112
|View full text |Cite
|
Sign up to set email alerts
|

Combination transarterial chemoembolization and radiofrequency ablation therapy for early hepatocellular carcinoma

Abstract: Background/Aims:We compared the recurrence of hepatocellular carcinoma (HCC) and the survival of patients who received radiofrequency ablation (RFA) after transarterial chemoembolization (TACE) with patients treated with TACE or RFA alone.Methods:This study included 201 patients with HCC, who were consecutively enrolled at Seoul St. Mary’s Hospital between December 2004 and February 2010. Inclusion criteria were a single HCC ≤ 5.0 cm or up to three HCCs ≤ 3.0 cm. We used a propensity score model to compare HCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 35 publications
3
46
1
2
Order By: Relevance
“…The propensity score model was determined by previous studies (8,11), the independent variables used in the matching included gender, age, alpha-fetoprotein (AFP) level, Child-Pugh score, alanine aminotransferase (ALT), tumor size and tumor number. Propensity score matching was performed using optimal matching method at the ratio of 1:2 (9).…”
Section: Discussionmentioning
confidence: 99%
“…The propensity score model was determined by previous studies (8,11), the independent variables used in the matching included gender, age, alpha-fetoprotein (AFP) level, Child-Pugh score, alanine aminotransferase (ALT), tumor size and tumor number. Propensity score matching was performed using optimal matching method at the ratio of 1:2 (9).…”
Section: Discussionmentioning
confidence: 99%
“…However, TACE alone results in incomplete tumor necrosis. Although the therapeutic efficacy of RFA of small HCC (i.e., < 3 cm) could be comparable to surgical operation [6,7], RFA has shown poor local tumor control when the tumor size exceeds 3 cm [8,9]. Therefore, the combination of TACE with radiofrequency ablation (RFA) may enhance efficacy against large HCC and prolong survival time in patients.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we believe that TACE treatment is relatively limited for CLM patients with potential surgical resection and is more suitable for the local treatment of tumors in unresectable patients. Nevertheless, some studies have shown that with a tumor diameter less than 3 cm, the long-term survival rate of patients treated with combined ablation is significantly better than that of patients treated with monotherapy, and the treatment effect is significantly improved compared with monotherapy[ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%